(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the adherence and behavior of the elderly and their families in relation to the consumption of cookies developed using passion fruit flour from the caatinga (P. cincinnata), for a period of 12 weeks. Method: This is a quantitative, descriptive and analytical study with a cross-sectional design. The study was carried out from November 2018 to February 2019, with 15 elderly people selected in three different groups, who would consume 30g of cookies daily for a period of 12 weeks, being monitored weekly. At the end of the consumption period, the acceptance of the cookies was evaluated, using the FACT attitude scale, as well as the purchase intention. In order to assess the food choices of the research participants, the Food Choice Questionnaire was used. Participants were asked about the interest of a family member in consuming the cookie. Results: The product was well accepted and most participants stated that they would buy it if it were available on the market. As for food choices, only the factor “ethical aspects” was not important for the participants. When asked about the interest of family members in consuming the cookies, 73.3% of the volunteers reported the interest of at least one family member. Conclusion: despite the long period of consumption, the research participants did not reveal rejection of the product, in addition to exposing family interest in its consumption.